Любимые стихи для малышей - Михалков Сергей Владимирович (Любимая книжка, 2015)
Экземпляры: ф.6 (20190809) / Инвентарный номер: 3092 И / Цена: / Сис.шифр: 84(2Рос=Рус)6-5 / Авт.знак: М 69 / ГРНТИ: 17.89.93 / ББК: 84(2Рос=Рус)6-5